(untitled) (Comprehensive Journal of Science, 2026)
Background: Postoperative pain remains a major clinical concern across different surgical procedures. Epidural anesthesia is commonly used; however, optimizing its analgesic efficacy remains a priority. Objectives: The current study aimed to evaluate the effect of epidural ketamine as an adjuvant on postoperative pain control and opioid requirement. Methods: A prospective cohort study was conducted on 150 patients undergoing cesarean section, inguinal hernia repair, and fracture neck of femur surgery. Patients were divided into two groups: Ketamine group (n=75), Control group (n=75). Ketamine, a well-known NMDA receptor antagonist, has been investigated as an adjuvant in epidural anesthesia to enhance analgesic efficacy and reduce opioid consumption. This study evaluates the pharmacological basis, clinical effectiveness, and safety concerns of epidural ketamine. While several studies demonstrate improved analgesia and opioid-sparing effects, concerns regarding neurotoxicity and inconsistent evidence limit its routine use. Further large-scale randomized controlled trials are needed to establish its safety and efficacy. Conclusion: Epidural ketamine is an effective adjuvant for postoperative analgesia, offering prolonged pain relief and reducing opioid consumption, with acceptable side effects.